Pengenalan Tari Tradisional Yosim Pancar pada Siswa-Siswi Sekolah Dasar Negeri 2 Abepura, Kota Jayapura, Provinsi Papua - Emilie M. I. Mansoben; Gerdha K. I. Numberi; Herdi Umbora; Katarina Abong Kia (JOURNAL SAINS STUDENT RESEARCH, 2024)
The introduction of Yosim Pancar Traditional Dance (Yospan) is carried out with the aim of introducing the dance as a Papuan cultural heritage that must be maintained and preserved. In the implementation of this activity in addition to providing material as a form of introduction of traditional Yospan dance to students and students of State Elementary School 2 Abepura, basic movements of Yospan dance are also practiced (Fast / Slow Yosim Movement, Seka Movement, Pacul Tiga Movement, Gale-gale Movement, Jeff Movement, and Pancar Movement). By introducing the Yosim Pancar (Yospan) social dance to students and teaching the basic movements of the Yosim Pancar dance is one of the manifestations of loving and preserving traditional dance culture in Papua. Equally important is to invite students to join the nearest dance studios around their neighborhood. As a recommendation, similar activities can be carried out in other schools in Papua.